Circular Economy in Selected EU Countries: Progress and Gaps - Sayegh, Marderos Ara; Danielewicz, Jan (Instal, 2025)
This study evaluates the progress of Circular Economy (CE) implementation across selected European Union (EU) Member States Germany, France, Italy, Spain, Poland, the Netherlands, and Sweden using a multi-indicator analytical framework over ten-year period from 2013 to 2023. Four key indicators are applied to assess national circular performance: Circular Material Use Rate (CMUR), Material Footprint (MF), Water Savings Potential (WSP), and Energy Recovery Potential (ERP). Results reveal substantial disparities in circular transition levels. The Netherlands and Italy emerge as leaders, demonstrating high CMUR values, efficient material use, and advanced recovery systems. France, Germany, and Spain show moderate but uneven progress, while Poland and Sweden remain below EU averages, indicating persistent circularity and efficiency gaps. A composite index and tiered ranking structure confirm a pronounced asymmetry between Western-Southern and Central-Nordic regions. The outcomes of this paper indicate that, despite progress in implementing the EU’s circular economy goals, the level of their implementation varies across the member states. Achieving the 2050 CE targets and sustaining progress beyond will require stronger coordination between national and EU strategies, greater industrial symbiosis, and sustained investment in circular infrastructure and innovation.
Keywords: Circular economy indicators; resources intensive industries; water sustainability; waste management; energy recovery